2012
DOI: 10.1002/hep.25852
|View full text |Cite
|
Sign up to set email alerts
|

Tracing hepatitis B virus to the 16th century in a Korean mummy

Abstract: A rare find of a mummified child from the 16th century AD, in Korea, with relatively preserved organs, enabled a search for ancient hepatitis B virus (aHBV) DNA sequences from laparoscopic-derived liver biopsies. Analysis of the complete aHBV genome (3,215 base pairs) revealed a unique HBV genotype C2 (HBV/C2) sequence commonly spread in Southeast Asia, which probably represents an HBV that infected the Joseon Dynasty population in Korea. Comparison of the aHBV sequences with contemporary HBV/C2 DNA sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(59 citation statements)
references
References 44 publications
2
49
0
Order By: Relevance
“…The ancient origin of HBV has been also confirmed by analysis of HBV sequences from two 16th century mummies and two recent studies, which detected HBV from ancient DNA samples, ranging in age from approximately 800 to 4,500 years (Mühlemann et al, 2018) and 1,000 to 7,000 years ago (Krause-Kyora et al, 2018), showed that the HBV infections were present for at least 7,000 years (Patterson Ross et al, 2018; Kahila Bar-Gal et al, 2012). As the major genotypes have probably originated before and during the onset of Neolithic and the subgenotypes during the later Neolithic period, the majority of HBV diversity has been accumulated as a result of dispersals following the antecedent ‘Out of Africa’ population migrations, which hosted and conveyed the parental HBV strains (Kramvis, 2014; Locarnini et al, 2013; Zehender et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…The ancient origin of HBV has been also confirmed by analysis of HBV sequences from two 16th century mummies and two recent studies, which detected HBV from ancient DNA samples, ranging in age from approximately 800 to 4,500 years (Mühlemann et al, 2018) and 1,000 to 7,000 years ago (Krause-Kyora et al, 2018), showed that the HBV infections were present for at least 7,000 years (Patterson Ross et al, 2018; Kahila Bar-Gal et al, 2012). As the major genotypes have probably originated before and during the onset of Neolithic and the subgenotypes during the later Neolithic period, the majority of HBV diversity has been accumulated as a result of dispersals following the antecedent ‘Out of Africa’ population migrations, which hosted and conveyed the parental HBV strains (Kramvis, 2014; Locarnini et al, 2013; Zehender et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…In 1976, scientists sequenced the first complete viral genome, enabling them to gather evidence of viral diseases from long before the modern era. In 2012 scientists used genetic sequencing techniques to identify a unique hepatitis B virus in a mummified child from 16th Century Korea (Kahila Bar-Gal et al 2012). Viruses have provided the tools to fuel investigations into genetics and molecular biology, and the steeply rising trajectory in scientific understanding has had widespread influence on medical diagnosis and treatment of infectious disease, allowing scientists to move beyond observation to actually altering aspects of human physiology.…”
Section: What the Public Needs To Know About Virusesmentioning
confidence: 99%
“…Emerging evidence shows that Hh signaling is activated in damaged liver, where it regulates tissue reconstruction. The level of Hh expression was shown to parallel the stages of liver disease [10], especially the degree of fibrosis. Recent studies demonstrated that apoptotic hepatocytes in patients and experimental animals with chronically damaged livers produced Hh ligands, which promoted the expansion of progenitors and induced the EMT (epithelial-to-mesenchymal transition) [11], [12].…”
Section: Introductionmentioning
confidence: 96%
“…In addition, Hh signaling is known to activate the transformation of quiescent hepatic stellate cells (Q-HSC) into myofibroblasts (MF)-HSCs [13]. Thus, Hh signaling is critically important in hepatic fibrogenesis [10], [13], [14], [15], [16], [17].…”
Section: Introductionmentioning
confidence: 99%